The Role of Learning Communities in Clinical Supervison for Internal Quality Assurance in Schools: A Systematic Literature Review - Fetti Kennisah Putri; Silvia Marniati; Besse Desi Amelia; Eva Iryani; Mohamad Muspawi; Denny Denmar (FKIP - Universitas Riau, 2026)
The development of learning communities and clinical supervision has transformed internal school quality assurance, despite challenges related to teacher competency, resistance, and limited managerial support. This study aims to analyze the role of learning communities in clinical supervision as a strategy for internal school quality assurance through a Systematic Literature Review (SLR) approach based on the PRISMA stages. The review systematically examines relevant literature to identify key themes, implementation challenges, and effective practices related to collaborative professional development and supervision in schools. The results show that the integration of learning communities and clinical supervision contributes to improving teacher pedagogical competence, strengthening collaboration, learning innovation, and strengthening the school's quality culture. The findings also indicate that reflective discussion, peer learning, and continuous feedback support more effective supervision and teacher professional growth. Thus, the integration of the two plays an important role in continuously improving the quality of education. The novelty of this study lies in highlighting the integration of learning communities and clinical supervision as a unified framework for internal school quality assurance. Unlike previous studies that examine these approaches separately, this review demonstrates their complementary role in fostering continuous improvement and sustainable educational quality enhancement.